Dach1 Mutant Mice Bear No Gross Abnormalities in Eye, Limb, and Brain Development and Exhibit Postnatal Lethality - Davis, Richard J. (American Society for Microbiology, 2001)
Drosophila dachshund is necessary and sufficient for compound eye development and is required for normal leg and brain development. A mouse homologue of dachshund, Dach1, is expressed in the developing retina and limbs, suggesting functional conservation of this gene. We have generated a loss-of-function mutation in Dach1 that results in the abrogation of the wild-type RNA and protein expression pattern in embryos. Homozygous mutants survive to birth but exhibit postnatal lethality associated with a failure to suckle, cyanosis, and respiratory distress. The heart, lungs, kidneys, liver, and skeleton were examined to identify factors involved in postnatal lethality, but these organs appeared to be normal. In addition, blood chemistry tests failed to reveal differences that might explain the lethal phenotype. Gross examination and histological analyses of newborn eyes, limbs, and brains revealed no detectable abnormalities. Since Dach1 mutants die shortly after birth, it remains possible that Dach1 is required for postnatal development of these structures. Alternatively, an additional Dach homologue may functionally compensate for Dach1 loss of function.